Problem Based Learning: An Experience of B.P. Koirala Institute of Health Sciences, Nepal - Baral, P; Koirala, S; Shrestha, S; Shah, S; Kumar, S; Baidya, R (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: Problem-based learning (PBL) is a kind of teaching- learning method in which students’ role is prime and they learn about a subject by active participation in problem solving.Methods: A total of 96 students studying in second year MBBS program were enrolled into present study. A questionnaire was given to students and they were asked to choose the option they felt about PBL methods. The questionnaire comprised of ten likert items out of which three were negative and seven were positive items.Results: Mean score for each statement in the questionnaire and the overall mean score were calculated. Overall mean score was 3.47.Conclusions: It was concluded that students of second year MBBS at BPKIHS, had a positive attitude towards PBL method of teaching-learning activity. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 42-45